(untitled) (Gilgameš, 2016)
This paper deals with a synchronic etymological analysis of both the epithets ‘μάχη κυδιάνειρα’ and ‘φθισίμβροτος’. In the first part, I analyse the term ‘κυδιάνειρα’. From a semantic perspective, this term cannot be interpreted as a possessive compound whose FM follows the Caland’s law, an observation that opens up other issues, which I tackle in my study. My hypothesis is that ‘κυδιάνειρα’ was probably formed by analogy on the example of other compounds which show °άνειρα as SM. In the second part, I analyse the term ‘φθισίμβροτος’ in order to verify Benveniste’s hypothesis that the verbal governing compounds with marked word-order, namely whit verbal FM, imply ‘an actual predicate of description’. Therefore, the battle should ‘destroy the mortals’ only – or especially – in those passages in which the battle is defined as ‘φθισίμβροτος’. Curiously, the only occurrence of ‘μάχη φθισίμβροτος’ (Ν339) is characterized by a rare insistence on the dangers of the battle; moreover, the occurrence of ‘αἰγὶς φθισίμβροτος’ (χ297) connotes the aegis as a signal of inexorable and oncoming death, as it is described in the passage (χ297-301). Although the occurrences of the term ‘φθισίμβροτος’ are very few, I conclude that the use of ‘φθισίμβροτος’ seems to uphold Benveniste’s hypothesis.